2013
DOI: 10.1631/jzus.b1300105
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional analysis of a novel ascorbate peroxidase (APX) gene from Anthurium andraeanum

Abstract: An 888-bp full-length ascorbate peroxidase (APX) complementary DNA (cDNA) gene was cloned from Anthurium andraeanum, and designated as AnAPX. It contains a 110-bp 5′-noncoding region, a 28-bp 3′-noncoding region, and a 750-bp open reading frame (ORF). This protein is hydrophilic with an aliphatic index of 81.64 and its structure consisting of α-helixes, β-turns, and random coils. The AnAPX protein showed 93%, 87%, 87%, 87%, and 86% similarities to the APX homologs from Zantedeschia aethiopica, Vitis pseudoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…MSA showed that highly conserved regions appeared on the N-terminal, while weakly conserved sequences existed on the C-terminal, as well as several conserved residues that constitute a potential active site for metal binding, were observed. These findings agree with the study of Liu et al (2013). In addition, the presence of a significant degree of conserved residues in the main sites of the enzyme has been demonstrated (Ozyigit et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…MSA showed that highly conserved regions appeared on the N-terminal, while weakly conserved sequences existed on the C-terminal, as well as several conserved residues that constitute a potential active site for metal binding, were observed. These findings agree with the study of Liu et al (2013). In addition, the presence of a significant degree of conserved residues in the main sites of the enzyme has been demonstrated (Ozyigit et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Accumulation of ROS will generate an oxidative stress condition, which leads to suppression of plant growth. However, plants have established their protection systems (nonenzymatic and enzymatic ROS scavenging systems) against such oxidative stress (Sharma et al, 2012;Liu et al, 2013). A nonenzymatic system employs antioxidants to diminish ROS such as glutathione (GSH), AsA, and flavonoids, while an enzymatic system utilizes many enzymes, including ascorbate peroxidase (APX), superoxide dismutase (SOD), glutathione reductase (GSH), and catalase (CAT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raj3765 displayed up to 203-fold level of expression at 42°C heat stress exposure. The expression level of tAPX during cold acclimation of wheat was upregulated [47]; the expression of A. andraeanum APX mRNA was evidently elevated by cold stress [48]; OsAPX2 expression of Oryza sativa was also developmental- and spatial-regulated and was induced by cold stress [49]. In this study, the expression levels of CaAPX were both remarkably upregulated under low and high temperature treatment (Figures 1(d) and 1(e)).…”
Section: Discussionmentioning
confidence: 65%
“…Subcellular localization of ScAPX6 in rice protoplast showed that ScAPX6::GFP was targeted at chloroplast (Figure 4 ), which was consistent with the result of bioinformatics predicted localization. Similar to other plant species, such as the APXs from Cucumis melo (Cheng et al, 2009 ) and A. andraeanum (Liu et al, 2013 ), ScAPX6 also contained a plant peroxidase like superfamily and the heme binding site and shared 94.29 and 82.93% similarities with the APX homologs from S. italic APX6 (XP_004973913.1) and S. bicolor APX6 (XP_002445876.1), suggesting that ScAPX6 belongs to a member of APX family.…”
Section: Discussionmentioning
confidence: 79%